Baseline Pupil Diameter Is Not a Reliable Biomarker of Subjective Sleepiness - Daguet, Inès; Bouhassira, Didier; Gronfier, Claude (Frontiers in Neurology, 2019)
Sleepiness is commonly seen as reflecting the basic physiological need to sleep and is associated with physiological and neurobiological changes. Subjective evaluations of sleepiness, however, are neither representative of cognitive and physical performances, nor of physiological sleepiness. Finding an objective and practical marker of sleepiness is essential in order to prevent errors, and accidents, but this has remained largely unsuccessful. The aim of this study was to determine whether the pupil diameter is a physiological biomarker of sleepiness at all times of day and to isolate the regulatory components involved. Twelve healthy men (20-29 years old) participated in a 56-h experimental protocol, including a 34-h constant routine paradigm with enforced wakefulness. This protocol was used in order to eliminate the potential influence of all environmental rhythms and reveal the endogenous circadian rhythmicity of two physiological measures: sleepiness and pupil diameter. Sleepiness was assessed subjectively every hour on a computerized 10 cm visual analogue scale and pupil size was recorded every two hours with a hand-held video-pupilometer. Our results revealed that sleepiness increased linearly with time awake and displayed a circadian rhythm. Pupil diameter showed a linear decrease with time spent awake as well as a circadian 24-h rhythm. This is the first evidence of a circadian variation of the baseline pupil size in constant dim light conditions. An overall negative correlation between the size of the pupil and the subjective level of sleepiness was observed. Analyzing the contribution of the two sleep regulation components in this correlation, we further showed: 1) a negative correlation between the homeostatic sleep pressure components, 2) a negative correlation between the circadian drives only during half of the 24-h period, corresponding to 75% of the biological day and 25% of the biological night. These results highlight that, due to the dual regulation of sleepiness by the homeostatic and circadian processes, pupil size is an index of sleepiness only at certain times and therefore cannot be used as a reliable biomarker of sleepiness.